2021
DOI: 10.1080/0144929x.2021.1955008
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging positive emotions to cope with technostress’s adverse effects: insights into the broaden-and-build theory

Abstract: This study investigates the role of positive performance feedback for information and communications technology (ICT) users, who could have either low or high levels of self-control. It could, moreover, explain the impact of that technological pressure on the users' performance, resulting in their achieving less. This study employs three techno-stressors, i.e. complexity, system errors, and work-overload in the experimental setting. By applying a contrast analysis, we confirm that the broaden-and-build theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In this study, we used the “broaden and build theory,” which proposes that accurately perceiving, using, managing, and regulating emotions help an individual develop self‐regulatory psychological resources such as resilience, allowing them to cope better with a stressful environment, including techno stressors (Alhothali & Al‐Dajani, 2022; Fredrickson, 2001; Sriwidharmanely et al., 2021; Zhai et al., 2022). Furthermore, Johnson et al.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…In this study, we used the “broaden and build theory,” which proposes that accurately perceiving, using, managing, and regulating emotions help an individual develop self‐regulatory psychological resources such as resilience, allowing them to cope better with a stressful environment, including techno stressors (Alhothali & Al‐Dajani, 2022; Fredrickson, 2001; Sriwidharmanely et al., 2021; Zhai et al., 2022). Furthermore, Johnson et al.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…This research model has game boosters' intellectual opportunism and OMSNs intervening to explain their intention to broaden and redo their business contracts. Moreover, this research posits Sagala and Sumiyana [76] and Sriwidharmanely et al [77] with a quasi-experiment. This study presents its three models in Figures 2(a)-2(c).…”
Section: Hypothesis Developmentmentioning
confidence: 55%
“…On the other hand, individuals with attached entities and insecure perspectives trigger self-validation goals, decreasing their learning performance. Therefore, this study posits Baum and Owen [47], Sher-Censor et al [16], Sriwidharmanely et al [48], and Sumiyana et al [49], who revealed that students with high-learning abilities could easily understand various levels of material compared to others. Moreover, they continue to make learning achievements, even utilising them in opportunistic conditions.…”
Section: Student Learning Attachment and Performancementioning
confidence: 75%